Situated circulation and publication languages of the academic elites of the Southern Cone - Beigel, Maria Fernanda (2022)
Situated circulation and publication languages of the academic elites of the Southern Cone This article analyzes the relationship between researchers’ self-perceptions about the value of publishing in English and the diversity of circulation practices observed in their entire publication trajectory. Methodologically, we use both a trinational survey carried out with the academic elite of Argentina, Brazil and Chile and an empirical observation of a sample of researchers’ resumes from these three countries. The contribution is twofold: in conceptual terms, we propose the concept of “situated circulation” as an alternative to linear and traditional perspectives of internationalization; In the empirical field, we show how the bibliodiversity in the academic trajectories and the multiscalarity of the circulation of these academics gives us a complex and diverse look in the three cases. As a consequence, the findings allow us to go beyond the usual views on English as a language of publication and advance the debate on the dynamism of the circulation process and its social-institutional anchors.